A study on the efficacy of TCA CROSS for the management of acne scars - Puri, Neerja (Journal of Pakistan Association of Dermatologists, 2016)
Objectives The purpose of this study was to evaluate the clinical effects of the CROSS method on atrophic acne scars in Indian patients. Patients and methods We selected twenty cases with ice pick scars from the department of dermatology for the study. Focal application of 70% TCA was done by pressing hard on the entire depressed area of atrophic acne scars using a sharpened wooden applicator. Results After treatment, marked improvement was seen in 60% patients, moderate improvement in 30% patients and mild improvement was seen in 10% patients. Regarding the side effects of treatment, erythema was seen in 15% patients, and stinging was noted in 10% patients and post-procedure hyperpigmentation was seen in none of the patients. Conclusions CROSS is a safe and very effective single modality for the treatment of atrophic acne scars with no significant complications.